Efek Latihan Streching terhadap Nyeri Sendi, Kekuatan Otot, Rentang Gerak Sendi Lansia di Wilayah Kerja Puskesmas Antang - Wahyuni, Sri; Rahim, Alfyan; Indargairi, Indargairi; Bubun, Juhelnita (Universitas Nusantara PGRI Kediri, 2022)
Pain is one of the complaints felt by the elderly when doing activities, especially the joint area. Stretching can restore muscle flexibility thereby reducing the sensation of pain. This activity aims to reduce pain in the joints, increase the range of motion of the joints so as to facilitate the mobilization of the elderly, increase the strength of the elderly, prevent contractures in the joints that are often experienced by the elderly. The method applied in this activity is to train dynamic-active stretching preceded by checking vital signs, measuring range of motion, pain intensity using VAS, and muscle strength. The result is stretching increases the range of motion, decreases the intensity of pain, increases muscle strength, so it can be concluded that streching is done 3-4 times a week and regularly will have a positive influence on the lives of the elderly to avoid physical mobilization disorders.